Komponen Kimia Cangkang Sawit (Elaeis guineensis Jacq.) dan Pengaruhnya terhadap Sifat Beton Ringan Chemical Components of Oil Palm (Elaeis guineensis Jacq.) Shell and Its Effect on Light Concrete Performance - Bambang Subiyanto; Hasan Basri; Linda Nurmala Sari; Triastuti Triastuti; Yetvi Rosalita (Masyarakat Peneliti Kayu Indonesia, 2007)
Recently, plenty of waste of oil palm shell as a lignocellulosic organic material was obtained due to increasing plantation of oil palm trees. However, utilization of oil palm shell still not optimally done and it has low economic value. In some countries, the lignocellulosic waste becomes a problem because it pollutes the environment. Many researches showed that oil palm waste can be used in several necessity products, such as, oil palm shell for active charcoal, stem and empty bunch for paper pulp, stem oil palm for furniture and particleboard. One of utilization of oil palm shell is as raw material for light weight concrete to replace sand; however, the mechanical properties were lower than standard.The purpose of this paper is to analyze chemical component of oil palm shell which affected the low mechanical properties of concrete made from oil palm shell. In this experiment, the oil palm shell, cement and sand were used as raw materials, then chemicals component of shell were analyzed from the shell that take from concrete made of oil palm shell. The percentage of shell to sand for making concrete was varied of 0%, 50%, and 100%. Then the shell was separated from the concrete, and chemical components were analyzed such as water content, ethanol benzene extraction with ratio 1 : 2, the solubility in hot water and cold water, lignin content, holocellulose content, and the strength of concrete. All of the testing was performed in 7 days and 28 days with two treatments to concrete (soaking in water at room temperature and keep in wet condition).The result of the experiments showed that the maximum composition of oil palm shell which used as filler of concrete is 50%; it gives impact strength nearly the same as concrete of control. The chemical component of extractive substance (fat) gives some influence to the compression strength of concrete